Power of QTL mapping of different genome-wide association methods for traits under different genetic structures: a simulation study - Garcia Neto, Baltasar Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The complexity of the traits that can present different genetic structures, such as polygenic or affected by genes of major effect, in addition to different heritabilities, among other factors, make the detection of QTLs challenging. Several methods have been employed with the purpose of performing genome wide association studies (GWAS), aiming the mapping of QTL. The single-step weighted GBLUP (wssGBLUP) method, for example, is an alternative to GWAS, which allows the simultaneous use of genotypic, pedigree and phenotypic information, even from non-genotyped animals. Bayesian methods are also used to perform GWAS, starting from the basic premise that the observed variance can vary at each locus with a specific priori distribution. The objective of the present study was to evaluate, through simulation, which methods, among the evaluated ones, more assist in the identification of QTLs for polygenic and major gene affected traits, presenting different heritabilities. We used the following methods: wssGBLUP, with or without additional phenotypic information from non-genotyped animals and two different weights for markers, where w1 represented the same weight (w1=1) and w2 the weight calculated according to the previous iteration process (w1); Bayes C, assuming two values for π (π = 0.99 and π = 0.999), where π is the proportion of SNPs not included in the model, and Bayesian LASSO. The results showed that for polygenic scenarios the detection power is lower and the additional use of phenotypes from non-genotyped animals may help in the detection, yet with low intensity. For scenarios with major effect, there was greater power in the detection of QTL by all different methods with slighter superior performance for the Bayes C method. However, the inclusion of additional phenotypic information caused bias in the estimates and harmed the performance of the wssGBLUP in the presence of major QTL. The increase in heritability for both structures improved the performance of the methods and the power of mapping. The most suitable method for the iii detection of QTL is dependent on the genetic structure and the heritability of the trait, and there is not a superior method for all scenarios.

A complexidade das características que podem apresentar diferentes estruturas de ação gênica como, por exemplo, poligênicas ou afetadas por genes de efeito maior, aliado a diferentes herdabilidades, entre outros fatores, tornam a detecção de QTLs desafiadora. Diversos métodos têm sido empregados com o intuito de realizar estudos de associação ampla do genoma (GWAS), objetivando o mapeamento de QTL. A metodologia weighted single-step GBLUP (wssGBLUP), por exemplo, é uma alternativa para a realização de GWAS, que permite o uso simultâneo de informações genotípicas, de pedigree e fenotípicas, mesmo de animais não genotipados. Métodos Bayesianos também são utilizados para a realização de GWAS, partindo da premissa básica de que a variância observada pode variar em cada locus em uma distribuição a priori específica. O objetivo do presente estudo foi avaliar, por meio de simulações, quais métodos, dentre os avaliados, mais auxiliaria na identificação de QTLs para características poligênicas e afetadas por genes de efeito maior, apresentando diferentes herdabilidades. Utilizamos os métodos: wssGBLUP, com a inclusão ou não de informação adicional fenotípica de animais não genotipados e dois distintos ponderadores para os marcadores, onde w1 representou a mesma ponderação (w1=1) e w2 a ponderação calculada de acordo com o processo de iteração anterior (w1) ; Bayes C, assumindo dois valores para π (π=0.99 and π=0.999), onde π é a proporção de SNPs não incluída no modelo, além do LASSO Bayesiano. Os resultados mostraram que para cenários poligênicos o poder de detecção é menor e o uso adicional de fenótipos de animais não genotipados pode ajudar na detecção, ainda que com pouca intensidade. Para cenários com característica sob efeito maior, houve maior poder na detecção de QTL pelos diferentes métodos em comparação aos cenários poligênicos com destaque para a leve vantagem do método Bayes C. A inclusão de informação fenotípica adicional, entretanto, causou viés nas estimativas e atrapalhou o desempenho do wssGBLUP na presença de QTL com efeito maior. O aumento da v herdabilidade para ambas as estruturas melhorou o desempenho dos métodos e o poder de mapeamento. O método mais adequado para a detecção de QTL depende da estrutura genética e da herdabilidade da característica, não existindo um método que seja superior para todos os cenários.
Poder de mapear QTL de diferentes métodos de associação genômica ampla para características com diferentes estruturas genéticas: estudo de simulação
Keywords: GWAS; Genetic Structure; wssGBLUP; Bayesian Methods; Estrutura Genética; Métodos Bayesianos